Anti‐apoptotic brain and reproductive organ‐expressed proteins enhance cisplatin resistance in lung cancer cells via the protein kinase B signaling pathway. Issue 2 (20th October 2015) - Li, Yang; Qi, Kang; Zu, Lingling; Wang, Min; Wang, Yuli; Zhou, Qinghua
Abstract: Background: Cisplatin‐based chemotherapy is the standard first‐line treatment for non‐small‐cell lung cancers (NSCLCs); however, the long‐term therapeutic effect is reduced by chemoresistance. Brain and reproductive organ‐expressed (BRE) proteins are overexpressed in several cancers and have an anti‐apoptotic function. However, their biological role in the development of the chemoresistant phenotype of human NSCLC remains unknown. We investigate the differential expression of the BRE gene in human lung adenocarcinoma cell lines A549 and the cisplatin‐resistant variant A549/cisplatin (DDP), and the mechanisms of cisplatin‐resistance induced by the BRE gene. Methods: Cell counting kit‐8 assay was employed to determine the sensitivity of A549 and A549/DDP cell lines to cisplatin. BRE expression was measured using quantitative real time‐polymerase chain reaction and western blot analysis. The apoptosis rate of lung adenocarcinoma cells was determined by flow cytometry. Results: BRE expression in A549 cells, derived from human lung cells, was markedly decreased compared with parental cisplatin‐resistant A549/DDP cells at messenger ribonucleic acid and protein levels. BRE overexpression in A549 significantly decreased sensitivity to DDP by inhibiting cell apoptosis. Conversely, BRE knockdown in A549/DDP cells increased their chemosensitivity. Importantly, we demonstrate that BRE overexpression induces the expression of phosphoprotein kinase B (p‐Akt) in lung cancer cells, while BRE silencing inhibits p‐Akt expression. Furthermore, downregulation of p‐Akt by LY294002 reversed the DDP resistance induced by BRE by increasing apoptosis. BRE enhances the DDP resistance of lung cancer cells through the Akt signaling pathway. Conclusion: Our findings provide new insight into the mechanism of DDP resistance in NSCLC cells and suggest BRE as an attractive new target for NSCLC treatment.